Measurement of dielectric constant of Zn1-x Mgx TiO3 (ZMT) ceramic material at microwave frequencies - Gangwar R.K.; Gupta P.; Singh S.P.; Kumar D. (My University, 2025)
In this paper measurement of real part of permittivity and loss tangent of Zn1-x Mgx TiO3 (ZMT) ceramics in S-band of microwave frequencies is presented and the associated accuracy estimated. This approach is based on the measurement of transmitted power from the cavity at and off resonance. Details of the design and fabrication of the rectangular cavity and the input and output coupling are given. The variation of dielectric properties of Zn1-x Mgx TiO3 with change in x-value is presented. The results of present work may provide useful design guidelines in the development of microwave components including dielectric resonator antennas. © 2008 IEEE.